Organics Acids from Cocoa Pod Waste Inoculated by Basidiomycota Fungi to Enhance the Performance of Shallots - Iradhatullah Rahim; Harsani Harsani; Hakzah Hakzah; Selis Meriem; Elkheir Hassaballah Abdallah Ahamed (AGRIVITA, Journal of Agricultural Science, 2022)
Excessive agricultural waste potentially causes serious pollution issues by farming practices. The potency of Basidiomycota’s fungi to degrade biomass for a safe practice might be considered to cope with this issue. This study aims to determine Basidiomycota fungi’s ability to produce organic acids after being inoculated on cocoa husks at various fermentation periods (20 and 40 days) and evaluate the effect of humic acid from those fermented cocoa husks on the growth and productivity of shallots. This research is carried out in three stages; the first is composting process from cocoa husks. The next is the acid-base extraction of cocoa pod husk compost to produce humic and fulvic acid. And the last is the application of humic acid to shallot plants. The results show that composting for 40 days produced higher levels of humic and fulvic acids. Inoculation with Coprinus sp produced the highest levels of humic acid but is not different with Pleurotus sp. Applying 100 ml/l of humic acid to shallots shows the best growth, while the concentration of 400 ml/l has the best production. This study presents the potential practice of cocoa pod residue and Basidiomycota fungi to increase agricultural commodities’ productivity agents.